Trichomoniasis in the brazilian population: prevalence, diagnosis and treatment - de Lacerda, Dhiego Alves; de Oliveira, Anaylle Vieira Lacerda; do Vale, Maria Eduarda Mulato; Celeste, Heitor Estrela; Cruz, Kayck Ryan Fernandes; Miranda, José Leonardo Frutuoso; Cavalcante, Ayla Alves; Neto, Valentim Fragoso de Freitas; Moreira, Anna Vitória Paz; Lustosa, Isabelle Lima (Revista Sistemática, 2024)
Trichomoniasis, caused by the protozoan Trichomonas vaginalis, is a sexually transmitted infection prevalent in the Brazilian population. This article reviews the epidemiology, diagnosis, and treatment of trichomoniasis in Brazil, highlighting the importance of prevention and proper management of this infection.